Exploring the experiences of stakeholders regarding the effectiveness of the Khomanani community partners programme in the social mobilisation of communities towards the prevention and care of HIV and AIDS - tlangelani@sfh.co.za (University of Pretoria, 2013)
Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2010.